L’utilisation De L’article 129 De La Loi Sur La Défense Nationale Dans Le Système De Justice Militaire Canadien - Cloutier, Jean-Bruno (Revue de droit de l'Université de Sherbrooke, 2004)
The thesis examines the nature and the relative gravity of the service offences contained in the Code of Service Discipline (CSD). The study reviews the classification of offences proposed by the several internal and external studies that have preceded the legislative reforms of the military justice system in 1997 and 1999. The author then proposes his own taxonomy of service offences.